Radiology training in Thailand: Challenges and innovations - Suphaneewan Jaovisidha (2018)
The Radiological Society of Thailand (RST) was founded in 1962 and renamed, The Royal College of Radiologists of Thailand (RCRT) in 1995 under the patronage of His Majesty King Bhumibol (RCRT 2009). As we present an overview of our radiology department and outline some of the challenges and innovations from our experience, we keep in mind that in some cases, it is the very existence of challenges that motivates us to develop innovative solutions. Our challenges in Thailand include: a shortage of radiologists throughout the country and most specifically in nonmetropolitan areas; English proficiency concerns; and logistical issues pertaining to the fact that our residents are spread out both within and outside of the institution. In this chapter, we address these challenges and discuss the innovative responses that we have developed: policies to ensure radiologists remain in nonmet-ropolitan areas; an English language proficiency course; and the creation of an E-learning website. © 2010 Springer-Verlag Berlin Heidelberg.